Application of the United Nations Framework Classification for Resources: Case Studies - United Nations Economic Commission for Europe (United Nations, 2020)
The United Nations Framework Classification for Resources (UNFC) is a project-based classification and management system applicable to all energy and mineral resource projects including renewable energy, anthropogenic resource projects as well as injection projects for geological storage. Since the adoption of the Sustainable Development Goals (SDGs), managing energy and raw material resources in a sustainable manner has become paramount to all stakeholders such as governments, companies and investors. This has to be viewed along with the Paris Climate Accord, which seeks low-carbon pathways in the appropriate developmental strategies. The book’s case studies demonstrate how UNFC could be used for sustainable resource management.